The secret adversary, with ebook eaudiobook - Christie, Agatha (Tantor Media, 2009)
Some secret plans have survived the sinking of the Lusitania , and amateur sleuths Tommy and Tuppence are on the trail of international spies in order to recover them. "Young Adventurers Limited" is a brand new private detective agency, set up by the dashing Tommy Beresford and the resourceful Tuppence Cowley. Their first assignment is to track down some secret documents that disappeared after the sinking of the Lusitania . Soon they are on the trail of the mysterious Mr. Brown, the head of an international gang of crooks—and in more danger than they bargained for!